2008
DOI: 10.1016/j.cellsig.2008.08.012
|View full text |Cite
|
Sign up to set email alerts
|

Expression, activity, and pro-hypertrophic effects of PDE5A in cardiac myocytes

Abstract: Cyclic GMP-selective phosphodiesterase type 5 (PDE5) has been traditionally thought to play little role in cardiac myocytes, yet recent studies using selective inhibitors such as sildenafil suggest it can potently modulate acute and chronic cardiac stress responses. To date, evidence for myocyte PDE5 expression and regulation has relied on small-molecule inhibitors and anti-sera, leaving open concerns regarding non-specific immune-reactivity, and off-target drug effects. To directly address both issues, we eng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
85
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 83 publications
(90 citation statements)
references
References 34 publications
(62 reference statements)
4
85
0
Order By: Relevance
“…Inhibition of PDE5 in the hypertrophied myocardium significantly improved myocardial contractility (17). Unlike previous reports, more recent studies have shown that PDE5A was expressed in the cardiomyocytes, and targeted inhibition of its activity with sildenafil modulated the cardiomyocyte hypertrophy response to phenylephrine treatment in vitro (27). Extrapolating these observations of cytoprotective effects to the bone marrow-derived mesenchymal stem cells (MSCs), we hypothesized that inhibition of PDE5A activity with tadalafil would promote cGMP/protein kinase G (PKG) activity to condition stem cells for improved survival and proliferation postengraftment in the infarcted heart.…”
mentioning
confidence: 60%
“…Inhibition of PDE5 in the hypertrophied myocardium significantly improved myocardial contractility (17). Unlike previous reports, more recent studies have shown that PDE5A was expressed in the cardiomyocytes, and targeted inhibition of its activity with sildenafil modulated the cardiomyocyte hypertrophy response to phenylephrine treatment in vitro (27). Extrapolating these observations of cytoprotective effects to the bone marrow-derived mesenchymal stem cells (MSCs), we hypothesized that inhibition of PDE5A activity with tadalafil would promote cGMP/protein kinase G (PKG) activity to condition stem cells for improved survival and proliferation postengraftment in the infarcted heart.…”
mentioning
confidence: 60%
“…The EmGFP linked to the artificial miRNA region was then transferred into pAd.CMV-DEST by recombinase cloning (Invitrogen). A control adenovirus (Ad.Neg-shRNA) containing EmGFP and a control shRNAmiR that was predicted not to target any known vertebrate gene was reported earlier (54). The initial viral amplification and purification was performed in our laboratory using an AdenopureLS adenovirus purification kit (Puresyn; Malvern, PA) according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Second, PDE5 inhibition suppresses Cn/nuclear factor of activated T cell (Cn/NFAT) signaling and expression of the genes encoding atrial and brain natriuretic peptides in isolated myocytes stimulated with a G q agonist (21,44). Third, knockdown of the gene encoding PDE5 in cardiac myocytes is antihypertrophic, having an impact similar to that of sildenafil, and the effect of combining both is similar to that of each alone (44). This last finding supports specificity of sildenafil for inhibiting PDE5.…”
Section: Figurementioning
confidence: 99%